Options for Agricultural Growth for Poverty Reduction in Nigeria - Diao, X.; Nwafor, M.; Alpuerto, V. (2009)
This study analyzes growth options in agricultural sub-sectors to accelerate overall economic growth and reduce poverty in Nigeria in the next nine years (2009-17) using an economy-wide, dynamic computable general equilibrium (DCGE) model. The model results show that if the individual agricultural subsectors' growth targets set by the Nigerian government can be achieved, the country will have 9.5 percent of agricultural annual growth and 8.0 percent of GDP growth in the next 10 years. The national poverty rate will fall to 30.8 percent by 2017, more than halving 1996's poverty rate of 65.6 percent, thereby accomplishing the objective for MDG1. The report emphasizes that in designing an agricultural strategy and in prioritizing growth, it is important to consider the following four factors at the subsector level: (i) the size of a subsector in the economy, (ii) growth multiplier effect through linkages of a subsector with the rest of the economy, (iii) poverty reduction - growth elasticity effect through growth primarily led by a subsector, and (iv) market opportunities and price effect for individual agricultural products.